Meningkatkan Partisipasi Ibu dalam Program Imunisasi Melalui Edukasi di Kelurahan Suka Raja - Syahrial, Luthfiyyah; Suryani, Des (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muslim Maros, 2023)
The decline in infant and under-five mortality rates is one of the indicators that determines the level of public health in Indonesia. This can be done by implementing an immunization program. However, the 35% lack of maternal participation in bringing children for immunization has resulted in a lack of immunization coverage in Suka Raja Village, so education is needed regarding the importance of immunization to improve children's health and prevent the transmission of diseases that can be prevented by immunization. This activity aims to eliminate mothers' concerns and doubts regarding the side effects of immunization, increase mothers' awareness regarding the importance of immunization, and encourage mothers' active participation in immunization programs to achieve optimal immunization coverage. Education is carried out using PowerPoint media accompanied by images to make it easier for participants to receive the information presented. The impact of this activity was assessed using a questionnaire and analyzed to determine the mother's willingness to participate in the child immunization program. Extension analysis shows an increase in maternal knowledge regarding immunization. It was concluded that this activity changed mothers' views regarding immunization, thereby increasing mothers' participation in the immunization program.